IMPLEMENTASI MODERASI BERAGAMA DI MIS MATHA’UL ANWAR CIBONGKOK MENES PANDEGLANG BANTEN - Martina; Musfiroh, Aam; Mutaqin, Mumu Zainal; Arifin, Muhammad (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to examine the extent to which religious moderation based on the values of wasathiyyah is implemented within the environment of MIS Mathla’ul Anwar Cibongkok, Pandeglang, Banten, particularly in the context of Islamic Religious Education. A qualitative approach was employed, with data collected from 110 students through direct observation, semi-structured interviews, documentation, and focus group discussions (FGDs) involving 3–5 students per group. In addition, field notes were taken by the researcher to capture undocumented observations. The findings reveal that the implementation of religious moderation policies at MIS Mathla’ul Anwar Cibongkok Menes, Pandeglang, Banten, is still strongly upheld by many students. This is largely attributed to the foundational religious upbringing provided by their parents. The study underscores that parents serve as the first educators for their children, instilling Islamic values and guiding them to avoid actions that deviate from shar’i (Islamic law). These findings can serve as a valuable reference for the development of parenting education programs organized by educational institutions across Indonesia.